COMPUTATIONAL STUDY OF CYCLONE FLOW FLUID DYNAMICS USING A DIFFERENT INLET SECTION ANGLE - Bernardo, S.; Peres, A. P.; Mori, M. (Revista de Engenharia Térmica, 2005)
The conventional design of the cyclone model has been used without significant modifications for about a century. Recently, some studies were carried out to improve equipment performance by evaluating the geometric influence of the tangential inlet section and scroll inlet duct design. In this work, the influence of cyclone inlet section geometry was studied using an angle of 45 degrees in relation to the cyclone body. The study was conducted for the gas and gas-particle phases, based on an experimental study available in the literature, where a conventional inlet section was used. Numerical experiments were carried out with the CFX computational code. The fluid dynamics profiles and tangential velocity component were evaluated for three inlet velocities (2.75, 7.75 and 15.2 m/s) using the Reynolds Stress model. The results showed that this proposal is useful for improving the cyclone performance.